COMPARISON OF GLOBAL WARMING POTENTIAL-IMPACT ON THE HANDLING OF THE HAZARDOUS-SLUDGE FROM THE CENTRALIZED INDUSTRIAL-WASTEWATER TREATMENT PLANT - Rijal Hakiki; Maryani Paramita Astuti; Temmy Wikaningrum (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2019)
Aim: This study aimed to compare the secured landfill method and thermally sludge treatment through gasification, in order to determine their environmental impacts. Methodology and Results: The gate-to-gate LCA method was the implementation approach used to determine the, limits and assumptions to the actual condition. The experimental, theoretical mass balance calculation and secondary data of previous researches were used to carry out this study, with open-source openLCA software. In addition, the LCA was made up of four phases which include goal and scope definition, inventory analysis, impact assessment, and data interpretation. The simulation showed that the implementation of the thermal gasification process reduced the emission released to the atmosphere by lowering the hazardous sludge volume which is directly transported to the secured landfill. Conclusion, significance and impact study: Several assumptions and adjustments were made to the simulation results using the openLCA software, in the determined scope of study. Therefore, in conclusion, the thermal (gasification) treatment of hazardous sludge is further studied in connection with its implementation at the treatment plant. This was indicated by the acquisition of global warming potential impact category of 673 kg CO2 eq for direct disposal to secured landfill, which reduced to 424 kg CO2 eq during the implementation of thermal treatment. Conversely, there is a reduction in magnitude of impact by 37%.